What do mindfulness scales measure? : expectation effects examined : a thesis presented in partial fulfilment of the requirements for the degree of Doctor in Psychology at Massey University, Albany, New Zealand - Ghanbari Noshari, Mona (Massey University, 2020)
The increasing popularity of mindfulness practices has seen an accompanying growth in research. However, most research has focused on the beneficial aspects of practicing mindfulness, but often without comparison to a control group, therefore the results that have been observed may not be “real” effects. In our current research, we aimed to see whether there were expectancy effects for mindfulness practice by designing two different studies and recruiting hundred and twenty participants to three different jigsaws (as a focused practice) groups: 1) Passive control group; which received no specific mention of mindfulness or mindfulness instruction in both studies, 2) Active control group; which received the label mindfulness on the task in study 1 (without any further intervention), and the introduction of negative information about mindfulness and possible downsides of practicing in study 2, and 3) Experimental group; which received actual mindfulness training in study 1, and positive information about mindfulness and advantages of practicing in study 2. A pretest and posttest design was employed using established self-report measures for mindfulness and wellbeing, in both studies of this research. The results indicated that supported expectancy effects for mindfulness as compared to the control condition. Also, while positive information led to improvements in scores compared to the control group, negative information led to a deterioration in scores compared to the control group. This research suggests that researchers need to be cautious in evaluating the self-reports of mindfulness practice due to expectancy effects.
Keywords: Mindfulness (Psychology); Research; 520401 Cognition